2007
DOI: 10.1111/j.1540-4560.2007.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Relations: Theory, Research, and Policy

Abstract: The dramatic increase in life expectancy and lowered fertility, especially in more advantaged countries, has resulted in people living longer and in more complex family structures. Other important changes affecting the family include greater geographical mobility, increased racial and ethnic diversity, new patterns of immigration and identity reformulation, as well as changing work and family roles. With reduced governmental resources available, it is especially important to understand the changing nature of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 24 publications
0
62
0
1
Order By: Relevance
“…The family social network constitutes, on the one hand, an important resource to protect individuals' health by, for example, reducing psychosocial stress and increasing one's overall well-being (e.g., Antonucci et al 2007;Franks et al 1992). Low relationship quality between parents and adult children (e.g., An and Cooney 2006;Koropeckyj-Cox 2002) or burdens associated with providing care to kin (e.g., Call et al 1999;Sherwood et al 2005), on the other hand, have been shown to result in health deterioration, especially if psychological well-being is considered.…”
Section: Intergenerational Family Relations and Healthmentioning
confidence: 99%
“…The family social network constitutes, on the one hand, an important resource to protect individuals' health by, for example, reducing psychosocial stress and increasing one's overall well-being (e.g., Antonucci et al 2007;Franks et al 1992). Low relationship quality between parents and adult children (e.g., An and Cooney 2006;Koropeckyj-Cox 2002) or burdens associated with providing care to kin (e.g., Call et al 1999;Sherwood et al 2005), on the other hand, have been shown to result in health deterioration, especially if psychological well-being is considered.…”
Section: Intergenerational Family Relations and Healthmentioning
confidence: 99%
“…In measuring social support, distinctions are made between actual support provided (enacted or received social support), and subjective assessments of support (perceived availability or adequacy of social support) (Barrera 1986). We have focused on subjective social support in this paper as evidence suggests that it is subjective assessments of support that have a stronger relationship with health and well-being (Antonucci and Jackson 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing complexity of family structures and dynamics can present challenges for recruitment in offspring studies. These issues include the following: greater geographic mobility of family members, increased racial/ethnic diversity, new patterns of immigration and identity reformulation, and changing work and family roles [11]. Few best practices exist to guide effective and efficient empirical approaches to participant recruitment.…”
Section: Introductionmentioning
confidence: 99%